Pembuatan Arang Aktif Kultur Jaringan Dari Pelepah Kelapa Sawit (Elaeis guineensis Jacq.) Dengan Berbagai Aktivator - Astuti, Cindy Sri; Azmi, Yudia; Febrianti, Febrianti (JURNAL PERTANIAN, 2024)
Palm fronds are widely available and have not been widely used. After being used, palm fronds can be processed into activated charcoal products. Activated charcoal can be used as an additive in tissue culture media which functions to remove toxic compounds. The aim of this research is to produce activated charcoal from oil palm fronds and commercial tissue culture with materials that meet the Indonesian National Standard (SNI 06-3730-1995) and to determine the type of activator that is suitable for making tissue culture. . Activated charcoal meets Indonesian national standards (SNI 06-3730-1995). The research design used was RAL with three treatments and three samples, namely A1 (5% NaCl solution activator), A2 (100% starfruit juice activator) and A3 (9% H3PO4 solution activator). The parameters observed were charcoal availability, humidity, ash, volatile matter and iodine absorption capacity. Research has shown that A3 (palm fronds activated with 9% H3PO4) can be used as activated charcoal. The correct treatment in this study was A3 with 9% H3PO4 activator. Palm frond activated charcoal contains 9% H3PO4 activator, 37.3% water content, 9.6% ash, 20.8% valuable substances and iodine absorption capacity of 742.4337mg/g. Keywords : Activated Charcoal, H3PO4, NaCl, Oil Palm Frond, Star Fruit Ekstract